Pengaruh PENGARUH IKLIM KERJA DAN MOTIVASI KERJA TERHADAP KINERJA DOSEN UNIVERSITAS BINA BANGSA GETSEMPENA - Sariakin; Nona Nofiana; Zahraini Zainal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to examine the lecturer performance model at Bina Bangsa Getsempena University based on the associative causal relationship between the independent variables, namely work climate and work motivation, and the dependent variable, namely lecturer performance. The method used is descriptive quantitative research with a correlational study approach. The research population consisted of 114 lecturers, and the sample taken randomly was 89 people. The instrument used was a questionnaire with a Likert scale, and data analysis was carried out using simple and multiple correlation and regression techniques. The research results show that the work climate has a positive and significant effect on lecturer performance with a correlation coefficient of 0.350 and a calculated t value of 3.480, providing an effective contribution of 16.03%. Work motivation also has a positive and significant effect with a correlation coefficient of 0.327 and a calculated t value of 3.231, providing an effective contribution of 25.57%. Apart from that, there is a positive and significant influence between work climate and work motivation together on lecturer performance with a correlation coefficient of R = 0.645 and a calculated F value of 11.75. To improve lecturer performance, it is recommended that leaders improve communication between lecturers and improve facilities and infrastructure that support lecturer motivation in carrying out their duties.